Physiotherapy Management for Early Mobilization after Total Hip Replacement Surgery E.C Secondary Osteoarthritis Hip: A Case Study - Akbar, Nisyahda Narpami; Supriyadi, Arin (Universitas Muhammadiyah Surakarta, 2023)
Introduction: In the lower extremities of the human body, there is a hip joint which is the most proximal part with the type of synovial ball and socket joint. In carrying out the functions, the hip joint often experiences problems both as a result of trauma, degenerative, and post-traumatic hip. Osteoarthritis (90%) contributes the largest problems in hip joint, followed by femoral neck fracture (5%), avascular necrosis (2%), dysplasia (2%), and inflammatory arthritis (1%) (Ferguson et al, 2018). Thus, if conservative treatment did not provide better changes, then a total hip replacement is performed to reduce pain and improve physical function. Total hip replacement is a surgical procedure by replacing the entire hip joint with an implant. Implants themselves can last up to 20 years. Case Presentation: A 58-year-old patient with unable to endure pain and discomfort in his activities and at rest, when consulted by a doctor, patients experience infections around implants and plates & screws. After total hip replacement patient complained of pain in the incision on the side of tight and limited movement in the left leg. Management and Outcome: Early mobilization given in the form of breathing exercises, isometric exercises, and other exercises on the bed, then on the second and third days began to be given transfer-ambulation exercises. Pain is measured using NRS and joint scope of motion is measured using a goniometer. Discussion: From several articles that become supporting in line with the results obtained where the initial mobilization is a major influence in the patient's life in the future. Patients who do initial mobilization are able to return to activity more quickly than patients who do not do initial mobilization. Conclusion: After receiving physiotherapy management for early moilization at three days after surgery, there was a decrease in pain levels, an increase in joint scope of motion, and a decrease in edema in the patient's left leg.